2015
DOI: 10.3138/jvme.0514-056r
|View full text |Cite
|
Sign up to set email alerts
|

Educational Interventions to Improve Cytology Visual Diagnostic Reasoning Measured by Eye Tracking

Abstract: The teaching of visual diagnostic reasoning skills, to date, has been conducted in a largely unstructured apprenticeship manner. The purpose of this study was to assess if the introduction of two educational interventions improved the visual diagnostic reasoning skills of novices. These were (1) the active use of key diagnostic features and (2) image repetition. A pre-test and post-test research design was used to compare the two teaching interventions to a traditional teaching group and an expert group using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Unfortunately, this did not translate into improved diagnostic accuracy in either group and this may reflect that short-term teaching interventions cannot replace the experience that comes with clinical practice and exposure to many patients with these findings. This finding was also eluded to by Warren et al 7 who found that active teaching with repeated case examples was more effective than traditional lecture style teaching.…”
Section: Discussionmentioning
confidence: 91%
“…Unfortunately, this did not translate into improved diagnostic accuracy in either group and this may reflect that short-term teaching interventions cannot replace the experience that comes with clinical practice and exposure to many patients with these findings. This finding was also eluded to by Warren et al 7 who found that active teaching with repeated case examples was more effective than traditional lecture style teaching.…”
Section: Discussionmentioning
confidence: 91%
“…However, using the eye tracker and the subsequent analysis, we have a better idea of the approach candidates use to reach their conclusion and the basis of their response in the image provided. In this case, studies on eye trackers have evaluated candidates’ interpretation of an electrocardiogram [ 24 ] or other medical images [ 22 , 23 ]. However, further research should bear in mind that gaze does not necessarily have a direct correlation with a complex cognitive process.…”
Section: Discussionmentioning
confidence: 99%
“…Similar time spent only in lecture did not provide the same benefit. 95 Students using a self-learning computer module to learn nasogastric intubation in a horse out-performed those taught via lecture plus live demonstration as assessed through knowledge tests, time to successful intubation, and confidence levels. 96 Langebaek and colleagues 97 evaluated which resources students used most frequently for a castration lab.…”
Section: Veterinary Medicinementioning
confidence: 99%